Trajectories of cultural innovation from the Middle to Later Stone Age in Eastern Africa: Personal ornaments, bone artifacts, and ocher from Panga ya Saidi, Kenya - (:unkn) unknown (My University, 2020)
African Middle Stone Age (MSA) populations used pigments, manufactured and wore personal ornaments, made abstract engravings, and produced fully shaped bone tools well before the so-called cognitive shift at 50,000 years ago (ka), formerly considered a key driver in the development of advanced human cultures. However, ongoing research across Africa reveals variability in the emergence of cultural innovations in the MSA and their subsequent development through the Later Stone Age (LSA). When present, it appears that cultural innovations manifest regional variability, suggestive of distinct cultural traditions. In eastern Africa, several Late Pleistocene sites have produced evidence for novel activities, but the chronologies of key behavioural innovations remain unclear. The 3 m deep, well-dated, Panga Ya Saidi sequence in eastern Kenya, encompassing 19 layers covering a time span of 78 ka beginning in late MIS 5, is the only known African site recording the interplay between cultural and ecological diversity in a coastal forested environment. Excavations have yielded worked and incised bones, ostrich egg shell beads, marine shell beads, worked and engraved ochre pieces, fragments of coral, and a belemnite fossil. Here we provide a detailed analysis of this material. We demonstrate that behavioural modernity on the eastern African coast is evident by 67 ka, and exhibits remarkable diversity and innovation through the LSA and Iron Age. We suggest the cultural trajectories evident at Panga ya Saidi were shaped by both regional traditions and cultural/demic diffusion.
Keywords: African Research